2022
DOI: 10.1073/pnas.2202857119
|View full text |Cite
|
Sign up to set email alerts
|

Sulfur radical formation from the tropospheric irradiation of aqueous sulfate aerosols

Abstract: The sulfate anion radical (SO 4 •– ) is known to be formed in the autoxidation chain of sulfur dioxide and from minor reactions when sulfate or bisulfate ions are activated by OH radicals, NO 3 radicals, or iron. Here, we report a source of SO 4 •– , from the irradiation of the liquid water of sulfate-containing organic aerosol particles under natural sunlight and laboratory UV radiation. Irradiation of aqueous sulf… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
15
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 13 publications
(15 citation statements)
references
References 83 publications
0
15
0
Order By: Relevance
“…HMS is known to be secondary in nature and can be formed from the nucleophilic addition of bisulfite (HSO 3 – ) or sulfite (SO 3 2– ) ion to formaldehyde (HCHO) in the aqueous phase. , While significant progress had been made regarding the understanding of abundance and formation mechanisms of HMS, its subsequent transformation kinetics and mechanisms remain unclear. HMS exhibits a surface affinity and tends to migrate to the air–liquid interface. ,, It adopts an arrangement with the methylene pointing out of the bulk (i.e., the bulk aerosol solution phase), the hydroxyl group pointing into the bulk, and the C–S bond pointing slightly out of the bulk. , This makes it more likely to be oxidized by gas-phase oxidants (e.g., hydroxyl radical (OH) and ozone (O 3 )) near the gas-aerosol interface (termed heterogeneous oxidation). In addition, OH oxidation of sulfonates (e.g., MSA) is known to produce inorganic sulfur species (e.g., sulfate (SO 4 2– ) ion). Given that sulfur in its inorganic and organic forms exhibit very different physicochemical properties including surface activity, water uptake, and cloud condensation nuclei activity, it is desirable to understand the conversion rates and mechanisms between the organic sulfur and inorganic sulfur forms upon oxidation.…”
Section: Introductionmentioning
confidence: 99%
“…HMS is known to be secondary in nature and can be formed from the nucleophilic addition of bisulfite (HSO 3 – ) or sulfite (SO 3 2– ) ion to formaldehyde (HCHO) in the aqueous phase. , While significant progress had been made regarding the understanding of abundance and formation mechanisms of HMS, its subsequent transformation kinetics and mechanisms remain unclear. HMS exhibits a surface affinity and tends to migrate to the air–liquid interface. ,, It adopts an arrangement with the methylene pointing out of the bulk (i.e., the bulk aerosol solution phase), the hydroxyl group pointing into the bulk, and the C–S bond pointing slightly out of the bulk. , This makes it more likely to be oxidized by gas-phase oxidants (e.g., hydroxyl radical (OH) and ozone (O 3 )) near the gas-aerosol interface (termed heterogeneous oxidation). In addition, OH oxidation of sulfonates (e.g., MSA) is known to produce inorganic sulfur species (e.g., sulfate (SO 4 2– ) ion). Given that sulfur in its inorganic and organic forms exhibit very different physicochemical properties including surface activity, water uptake, and cloud condensation nuclei activity, it is desirable to understand the conversion rates and mechanisms between the organic sulfur and inorganic sulfur forms upon oxidation.…”
Section: Introductionmentioning
confidence: 99%
“… 18 , 19 Although the atmospheric concentration of the SO 4 •– radical has not been directly measured, it has been estimated between 9.1 × 10 –13 and 5.5 × 10 –17 M, assuming known sources. 4 New mechanisms of reactive sulfur species relevant to sulfate aerosols have been recently reported, including SO 4 •– formation from irradiated sulfate aerosols, 20 OH-initiated oxidation of organosulfates, 21 and autocatalysis of the SO 4 2– anion in the presence of phenols. 22 The formation of reactive sulfur was also reported from the interfacial redox of ammonium sulfate aerosol particles.…”
Section: Introductionmentioning
confidence: 99%
“…•− formation from irradiated sulfate aerosols, 20 OH-initiated oxidation of organosulfates, 21 and autocatalysis of the SO 4 2− anion in the presence of phenols. 22 The formation of reactive sulfur was also reported from the interfacial redox of ammonium sulfate aerosol particles.…”
Section: ■ Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…There are a number of potential organosulfate-forming mechanisms in the atmosphere, including ring-opening nucleophilic addition of sulfate to epoxides, nucleophilic substitution of organonitrates by sulfate, , and sulfate radical addition to alkenes. In the pioneering atmospheric chamber experiments by Surratt et al, because organosulfate formation was positively correlated with SOA acidity, it was suggested that organosulfates form by sulfate esterification of alcohols . In this reaction, an alcohol group in the reactant is replaced by a sulfate group under strong acid catalysis conditions.…”
Section: Introductionmentioning
confidence: 99%